Towards quantitative mesh pre-optimization for finite element analysis. Issue 4 (7th June 2017) - Cuillière, Jean-Christophe; Francois, Vincent
ABSTRACT: In a previous research work, we introduced the concept of automatic mesh pre-optimization, also referred to as a priori mesh adaptation. Indeed, the basic idea underlying mesh pre-optimization is providing finite element analysis with meshes that have been adapted before analysis itself. It consists in automatically deriving mesh sizing functions from geometric features of the analysis domain. This allows providing the analyst with meshes that feature a certain degree of adaptation around sensitive zones or sensitive shapes (high curvature zones, narrow regions, sources of stress concentration, etc.) before any analysis, which also means before any a posteriori mesh adaptation. So far, mesh pre-optimization could not be considered as a quantitative adaptation since it does not explicitly target accuracy objectives, contrary to a posteriori mesh adaptation methods. This paper brings about new concepts in mesh pre-optimization that tend to make pre-optimization not only qualitative. It shows that, for 2D features, quantitative accuracy objectives in finite element analysis can reasonably be met, without using a posteriori adaptation. The approach proposed is applied in the context of plane stress analysis and it shows that user specified accuracy objectives can automatically be achieved at stress concentration locations. This improvement of mesh pre-optimization should not be regarded as an alternative to a posteriori adaptation but as an efficient way to obtain accurate preliminary FEA results, which is particularly interesting when evaluating design scenarios. GRAPHICAL ABSTRACT: